A Study On Occupational Stress Experienced By Lecturers Of The Higher Learning Institutions - Baskaran, Subramaniam (2004)

(untitled)
This is a study on occupational stress experienced by lecturers of the higher learning institutions in the state of Perlis. It has five main objectives. The first objective is to determine the average level of job stress experienceld by lecturers of various higher learning institutions in the state of Perlis. The second objective is to determine the most common factors (stressors) that caused job stress of the lecturers. While the third objective is to determine whether there is a significant difference in term of the occupational stress level experienced by the type A behavior pattern and type B behavior pattern lecturers. Next, its’ fourth objective is to determine the association between personality type (type A or type B) among the lecturers and their occupational stress level. Last but not least, the fifth objective is to determine whether there are significant differences in term of the occupational stress levels experienced by different subgroups of the demographic factor, such as, age, gender, work experiences and marital status. The result of the findings of this study showed that; (a) generally, the lecturers of the higher learning in the state of Perlis were experiencing low level of occupational stress. (b) the most common factors that caused occupational stress among the lecturers were job overload, job nature and time management. While in term of the association, reward system (r = 0.663, p= 0.000) and relationship (r = 0.649, p = 0.000) seemed to show stronger correlations with occupational stress level. (c) there was a significant difference between the mean level of the TABP and TBBP resplondents of this study ( p value < 0.05). There was also a significant positive correlation between TABP respondents and the level of occupational stress (r = 0.197, p = 0.043). (d) it was also clear that there were no significant differences in the occupational stress levels among the different subgroups of the demographic variables such as sex, age groups, work experiences and marital status (p value > 0.05). Based on the research findings, it is recommended that organizations concerned should help the lecturers to achieve mental, emotion and physical preparedness to cope with 0s effectively.